Palaeomagnetic and rock magnetic studies on the dykes of Goa, west coast of Indian Precambrian Shield - Patil, S. K.; Rao, D. R. K. (My University, 2002)
Detailed alternating field (AF) and thermal demagnetization techniques on 120 samples belonging to 10 dykes of the Goa region along the west coast of the Indian Precambrian Shield, have yielded characteristic remanent magnetization (ChRM) directions from 9 dykes of which 6 dykes exhibited a reverse magnetic polarity direction (D=150°, I=44.30°, k=58, α95=5.8, N=6 dykes), while 3 dykes exhibited normal polarity D=351°, I=−50°, k=21, α95=14.9, N=3 dykes) direction. The remaining 1 dyke has shown stable direction, but with a strong overprint of the present earth field (PEF) direction, which could not be removed by either AF or thermal cleaning techniques. A Palaeomagnetic pole, computed by averaging the VGPs of 9 dykes is situated at 41.2°N 78.1°W (N=9 dykes; A95=9.81°), which is close to that of the Deccan super pole (36.9°N, 78.8°W), suggesting that the dykes in the Goa region are related to the Deccan basaltic eruptions. Recently published dating on the normal polarity dykes of the studied area have assigned the ages as 62.8±0.2 Ma. These results demonstrate that the Deccan magnetism continued to affect western India for at least 1–2 Ma after the peak Deccan eruption during the K–T boundary. On the basis of published geological and geochemical information along with our Palaeomagnetic results, these intrusive bodies could be attributed as the feeders for the uppermost formations of Wai subgroup of the Western Ghat Deccan basalts, or to the major geodynamic events such as the opening of the Arabian Sea and the rifting of the Seychelles–Mascarene oceanic plateau, which occurred soon after the cessation of the Deccan volcanism. Rock magnetic experiments such as the Lowrie–Fuller test along with low-temperature magnetic susceptibility and isothermal remanent magnetization (IRM) measurements have identified single domain (SD) type titano-magnetite as the major characteristic remanent magnetization carrying magnetic mineral in the dyke samples.
Keywords: Palaeomagnetism; Deccan traps; Precambrian Shield; Feeder dykes; K–T boundary